UPAYA PENINGKATAN PEMAHAMAN SANTRIWATI DENGAN PENYULUHAN TENTANG MENSTRUASI DI PONPES NURUL HAKIM KECAMATAN KEDIRI KABUPATEN LOMBOK BARAT - Atika Maelinda Larasati; Candra Eka Puspitasari; Nadia Saptarina (Universitas Mataram, 2023)
Adolescents is a transition from childhood to adulthood which affects the ability to observe science. Knowledge is a factor in shaping behavior and actions, so that adolescents who enter their menstrual period will behave to maintain cleanliness during menstruation. Menstruation is the process of discharge of blood from the vagina which is very easily infected. The most common disorder is leucorrhoea, priuritus vulvae, which in the long term can cause cervical cancer. But it can be prevented by maintaining personal hygiene during menstruation. This service aims to increase the understanding of female students during menstruation at the Nurul Hakim Islamic Boarding School. With that students can prevent the onset of the disease that will occur. The method of implementing this socialization is in the form of lecture methods and interactive discussions. This socialization began with delivering material related to menstruation and distributing validated questionnaires in the form of pre-tests and post-tests for each Santriwati. The results of filling out the pre-test and post-test questionnaires obtained from a total of 64 respondents respectively 54% and 61% were processed using Microsoft Excel. From the results of the hypothesis testing that has been done, it shows that there is no significant difference between the scores of knowledge about menstruation before and after counseling. But it can be said to have an increase that is not quite far between before and after counseling. The conclusion from this activity was that there was a significant increase when conducting counseling at the Nurul Hakim Islamic Boarding School, Kediri District, West Lombok Regency.